Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41420-020-0279-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinase inhibition of G2019S-LRRK2 enhances autolysosome formation and function to reduce endogenous alpha-synuclein intracellular inclusions

Abstract: The Parkinson's disease (PD)-associated kinase Leucine-Rich Repeat Kinase 2 (LRRK2) is a crucial modulator of the autophagy-lysosome pathway, but unclarity exists on the precise mechanics of its role and the direction of this modulation. In particular, LRRK2 is involved in the degradation of pathological alpha-synuclein, with pathogenic mutations precipitating neuropathology in cellular and animal models of PD, and a significant proportion of LRRK2 patients presenting Lewy neuropathology. Defects in autophagic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 68 publications
3
55
0
Order By: Relevance
“…It has been extensively reported that both aSyn and LRRK2 affect the autophagic process (Bellomo et al, 2020; Bravo-San Pedro et al, 2013; Ho et al, 2019; Schapansky et al, 2014). Furthermore, we recently found that the reduction of pS129-aSyn-positive inclusions in G2019S-LRRK2 cells, following exposition to a LRRK2 kinase inhibitor, depends on correct lysosomal activity(Obergasteiger et al, 2020). As an unbiased approach we used the RT² Profiler™ PCR Array for autophagy to measure the gene expression levels of 84 genes implicated at different stages of the ALP.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been extensively reported that both aSyn and LRRK2 affect the autophagic process (Bellomo et al, 2020; Bravo-San Pedro et al, 2013; Ho et al, 2019; Schapansky et al, 2014). Furthermore, we recently found that the reduction of pS129-aSyn-positive inclusions in G2019S-LRRK2 cells, following exposition to a LRRK2 kinase inhibitor, depends on correct lysosomal activity(Obergasteiger et al, 2020). As an unbiased approach we used the RT² Profiler™ PCR Array for autophagy to measure the gene expression levels of 84 genes implicated at different stages of the ALP.…”
Section: Resultsmentioning
confidence: 99%
“…1 ng of cDNA was used for each reaction to asses RIT2 mRNA gene expression (Hs01046671_m1, FAM), multiplexed with a housekeeping gene (RPP30, HEX, BioRad cat# 10031243). PCR was carried out as suggested by the manufacturer using ddPCR Supermix for probes (BioRad, cat# 11969064001 The autophagy gene expression array (PAHS-084Z, Qiagen) for G2019S-LRRK2 cells without and with RIT2 overexpression was carried out according to the manufacturers protocol and as described in (Obergasteiger et al, 2020). Quantitative PCR was performed in a CFX96 Touch™ Real-Time PCR Detection System (BioRad).…”
Section: Droplet Digital Pcr and Autophagy Qpcr Arraymentioning
confidence: 99%
See 3 more Smart Citations